PENGUJIAN FINANCING TO DEPOSIT RATIO (FDR) SEBAGAI MEDIASI ANTARA PEMBIAYAAN, NON PERFORMING FINANCING (NPF) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP LABA PADA BANK UMUM SYARIAH INDONESIA - Rika Lidyah; Oki Sania Riski; Dwithia Chan Yo Putri; Tri Agustina (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2019)
This study aims to determine the effect of financing, non-performing financing (NPF) and operating income operating expenses (BOPO) on profits with financing to deposit ratio (FDR) as a mediating variable at Islamic Commercial Banks in Indonesia. The type of data used is secondary data with an external type. Sources of data in the form of annual financial reports (annual report) Islamic Commercial Bank. The number of samples of 7 companies with a sample determination method that is purposive sampling. Data analysis techniques used are the classical assumption test and path analysis. Research found that (1 ) financing has a significant negative effect on FDR, (2) NPF has no effect on FDR, (3) BOPO has a significant negative effect on FDR, (4) financing has a significant positive effect on earnings, (5) NPF has a significant negative effect on earnings, (6) BOPO has no effect on earnings, (7) FDR has a significant negative effect on earnings, (8) FDR mediates the effect of financing on earnings, (9) FDR does not mediate the effect of NPF on earnings and (10) FDR mediates the influence of BOPO on earnings.